Latino & Muslim in America: race, religion, and the making of a new minority$Harold D. Morales. American Academy of Religion - Morales, Harold D. (Religion, culture, and history, 2018)
Latino and Muslim in America examines how so called "minority groups" are made, fragmented, and struggle for recognition in the U.S.A. The U.S. is currently poised to become the first nation whose collective minorities will outnumber the dominant population, and Latinos play no small role inthis world changing demographic shift. Even as many people view Latinos and Muslims as growing threats, Latino Muslims celebrate their intersecting identities both in their daily lives and in their mediated representations online. In this book, Harold Morales follows the lives of several Latino Muslim leaders from the 1970's to the present, and their efforts to organize and unify nationally in order to solidify the new identity group's place within the public sphere. Based on four years of ethnography, media analysis andhistorical research, Morales demonstrates how the phenomenon of Latinos converting to Islam emerges from distinctive immigration patterns and laws, urban spaces, and new media technologies that have increasingly brought Latinos and Muslims in to contact with one another. He explains this growingcommunity as part of the mass exodus out of the Catholic Church, the digitization of religion, and the growth of Islam. Latino and Muslim in America explores the racialization of religion, the framing of religious conversion experiences, the dissemination of post-colonial histories, and thedevelopment of Latino Muslim networks, to show that the categories of race, religion, and media are becoming inextricably entwined